2023
DOI: 10.3390/nu15020356
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Probiotics Administration Attenuates Gastrointestinal Complications and Gut Microbiota Dysbiosis Caused by Chemotherapy in Colorectal Cancer Patients

Abstract: The current study aims to evaluate the potential roles of taking probiotics postoperatively in attenuating the gastrointestinal complications and disturbed gut microbiota in colorectal cancer (CRC) patients undergoing chemotherapy. One hundred eligible CRC patients who were treated with radical surgery and needed to receive chemotherapy were recruited. Half of them were randomly assigned to the Probio group to take a probiotic combination from post-operation to the end of the first chemotherapeutic course. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 33 publications
1
51
0
1
Order By: Relevance
“…65 Besides, Blautia could also promote the production of SCFAs, particularly by increasing butyrate level in colorectal cancer patients after postoperative probiotics administration. 68 In our study, Bacteroides was positively correlated with acetic acid and isobutyric acid and negatively correlated with isovaleric acid. Blautia was positively correlated with butyric acid.…”
Section: Papersupporting
confidence: 51%
“…65 Besides, Blautia could also promote the production of SCFAs, particularly by increasing butyrate level in colorectal cancer patients after postoperative probiotics administration. 68 In our study, Bacteroides was positively correlated with acetic acid and isobutyric acid and negatively correlated with isovaleric acid. Blautia was positively correlated with butyric acid.…”
Section: Papersupporting
confidence: 51%
“…Jiang et al found that a probiotic combination ( Bifidobacterium longum , Lactobacillus lactis , and Enterococcus faecium ) can ameliorate the severity of oral mucositis via gut microbiota modulation for nasopharyngeal carcinoma patients who were undergoing concurrent radiochemotherapy 28 . Probiotic combinations containing Bifidobacterium infants , Lactobacillus acidophilus , Enterococcus faecalis , and Bacillus cereus have also been shown to be effective in attenuating chemotherapy‐related gastrointestinal complications, especially diarrhea for colorectal cancer patients who were undergoing postoperative chemotherapy 22 . As for lung cancer patients receiving platinum‐based doublet chemotherapy, Clostridium butyricum can relieve chemotherapy‐related diarrhea 25 .…”
Section: Discussionmentioning
confidence: 99%
“…After one cycle of chemotherapy and compound probiotic supplement/placebo treatment, the scores of the two groups (group BP-1 vs. group C) showed a statistically significant difference in the following dimensions: overall quality of life (75.45 ± 15.46 vs. 61.55 ± 19.12, p = 0.001), pain (6.76 ± 13.87 vs. 17.75 ± 25.68, p = 0.021), nausea and vomiting (4.05 ± 9.13 vs. 22 2a).…”
Section: Eortc Qlq C30 Questionnaire Analysismentioning
confidence: 95%
See 1 more Smart Citation
“…4 Recently, the role of probiotics in CRC has attracted widespread attention. 5 Lactobacillus plantarum ( L. plantarum ) is a probiotic strain that is commonly found in the vagina and gastrointestinal tract and commonly encountered in dairy products. 6 Previous investigations have indicated that L. plantarum exhibits anti-inflammatory properties by inhibiting proinflammatory cytokines and bolstering the integrity and function of the intestinal epithelial barrier.…”
Section: Introductionmentioning
confidence: 99%